Interleukin-6 and Diabetic Retinopathy: A Systematic Review and Meta-Analysis. (4th May 2019) - Yao, Yang; Li, Rong; Du, Junhui; Long, Lihui; Li, Xiangnan; Luo, Na
ABSTRACT: Background : Interleukin-6 (IL-6) is produced by a variety of cells involved in inflammation and acts as local intensification signals in pathological processes associated with chronic eye inflammation. This meta-analysis was performed to provide a better understanding of the relationship between IL-6 and diabetic retinopathy. Methods : The study was started with systematic search for literatures by using the PubMed, Web of Science and Embase online databases. The standard mean difference (SMD) and its 95% confidence intervals (CIs) were was included and then pooled with a random effects model. Results : Thirty-one articles, containing1099 DR patients and 1010 controls, were included in this meta-analysis. The level of IL-6 in the DR group was found to be higher than that in the control group (SMD: 2.12, 95% CI: 1.53−2.70, p < 0.00001).Obvious heterogeneity existed between the studies ( p < 0.00001, I 2  = 96%). So a subgroup analysis and sensitivity analysis were performed. Removing the sensitivity studies, the stability of the overall treatment effect was good. Subgroup analysis showed that the levels of IL-6 in case group were observed to be higher than those in the control group; and the IL-6 levels in the proliferative diabetic retinopathy (PDR) group were also higher than those in the non-proliferative diabetic retinopathy (NPDR) group. (SMD: 0.78, 95% CI: 0.26–1.31, p =  0.003) Conclusion : The results from this current meta-analysis indicated that increased level of IL-6 generally exist in DR patients. And it may associated with the severity of DR. However, large-scale and high-quality studies in future are required to confirm the present findings.